1996
DOI: 10.1002/(sici)1097-0142(19961201)78:11<2388::aid-cncr18>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic phenotype correlates with high expression of membrane-associated complete β-human chorionic gonadotropin in vivo

Abstract: BACKGROUND. Investigations using living human cancer cells and the nude mouse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…18 -25 In studies on the hCG␤ subunit, no expression has been found in non-neoplastic mucosa of the rectosigmoid colon or in benign colorectal neoplasms. 4,26,27 According to several reports, hCG production is associated with more aggressive behavior in non-trophoblastic tumors. 18,28,29 Other studies indicate that hCG expression is of limited prognostic value.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 -25 In studies on the hCG␤ subunit, no expression has been found in non-neoplastic mucosa of the rectosigmoid colon or in benign colorectal neoplasms. 4,26,27 According to several reports, hCG production is associated with more aggressive behavior in non-trophoblastic tumors. 18,28,29 Other studies indicate that hCG expression is of limited prognostic value.…”
mentioning
confidence: 99%
“…2,3 The presence of hCG in any of its forms is an in vivo phenotypic characteristic of human cancer cells. 4 Intact hCG appears to be the main form of hCG immunoreactivity (hCG-IR) during growth and local invasion of a tumor, whereas expression of the free ␤ subunit (hCG␤) correlates more closely with a metastatic phenotype. 4 hCG-IR has been detected in a wide variety of non-trophoblastic neoplasms in both tumor cells [5][6][7] and serum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 This work was performed using human tumors grown in nude mice. In addition, others have shown that cell membrane-associated HCG␤ identifies a subgroup of prostate adenocarcinoma patients with a poor prognosis, regardless of the histologic grade of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Acevedo et al 4,5 demonstrated that cultured human cancer cells expressed HCG on the cell mem-brane and suggested a direct correlation between the extent of membrane-associated HCG and the metastatic potential of the cells. Kellen et al 6 demonstrated that adenocarcinoma cells have significantly diminished tumorigenicity when inoculated into mice previously exposed to HCG conjugated to a tetanus toxoid intended to prophylactically stimulate an immune response against HCG-like substances.…”
Section: Introductionmentioning
confidence: 99%